Культурно-мистецькі часописи в реаліях незалежної України - Нестеренко, П.В. (Слово і Час, 2019)
У статті вперше розглянуто художнє вирішення обкладинок київських часописів (1980-ті й до теперішнього часу). Проаналізовано час і обставини їхнього виходу в світ, злагоджену роботу авторського колективу, визначено мету й завдання. Висвітлено важливу роль часописів у мистецькому й культурно-освітньому житті незалежної України. During the years of independence the diversity in the opinions on many important issues – the role of an artist and art in the world, the solution of the crucial contemporary problems, the understanding of the national characteristics – became particularly acute. This contributed to the revival of some old journals and creation of many new ones. Unfortunately, today’s typical situation with an extravagant appearance of the next new edition and its short-term existence is reminiscent of the events that took place nearly hundred years ago. Numerous periodicals were born at that time and then quickly disappeared and went into oblivion. Over time, when it turned out that outstanding, though hidden from public, artists worked on their design and artistically determined the era, many journal covers were at last evaluated as achievement of Ukrainian art. However, the modern authors of the covers and the general concept of numerous journals remain on the margins of the artistic process as well. As a consequence, the question arises: do we really have to wait decades to properly evaluate their high art? Despite the short age, artistic and other journals added a bright page in the cultural and educational life of independent Ukraine. They objectively covered the achievements of Ukrainian artists and will serve as an important material for further research on the history of the Ukrainian art. A skillfully designed logo accompanied by a well-chosen and composed work of art or its fragment became a true decoration of contemporary journals. In this regard, the author of the paper considers the artistic designs of the covers used in Kyiv journals (from 1980s up to now) and identifies the best masters working in this field. Attention is paid to the time and circumstances of their release, the coordinated work of the authors and editors, the purposes and tasks of the editions. The important role of periodicals in the artistic and educational life of independent Ukraine is highlighted.